MANIFESTATION OF NATURALISM IN THE SHORT STORY MAT PISAU BY EKA KURNIAWAN - Jalu Norva Illa Putra (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Literature is the only thing capable of depicting a social reality. Through literature, feelings can be conveyed in their entirety, including the depiction of oppression that cannot be resisted. The marginalized class is a class that is oppressed and determined. This study aims to examine determination in the short story Mat Pisau by Eka Kurniawan. This study will use the theory of The Trinity of Forces by Émile Zola. The main focus of this study is to explore how the child character, Mat Pisau, is depicted as a subject determined by internal and external factors so that he is unable to escape the shackles of oppression. The method used is descriptive qualitative with an objective approach to the text. The results of the study show that Mat Pisau's oppression is absolute and systematic, which is influenced by three main variables. First, heredity in the form of inherited poverty and negative social labels from the family. Second, the toxic social milieu (environment) at school and home that perpetuates the practice of bullying. Third, the moment (context) in the form of a violent tragedy that destroys Mat Pisau's false identity. The research findings reveal that Mat Pisau's attempt to gain existence through knife skills is merely a temporary anomaly that ultimately fails to defy the laws of naturalism. Mat Pisau represents the